2016
DOI: 10.1177/1066896916657590
|View full text |Cite
|
Sign up to set email alerts
|

Complete Tissue Submission to Increase Lymph Node Detection in Pelvic Lymph Node Packets Submitted for Patients Undergoing Radical Prostatectomy and Radical Cystectomy

Abstract: Submitting all additional fatty tissue after palpable identification of LNs can significantly increase the detection of LNs in RP and RC cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…In a previous survey on PCa conducted by the International Society of Urological Pathology (ISUP), 27% of members submitted the entire PLND specimen . Not surprisingly, studies have shown that total embedding can increase the nodal yield following RP and RC and may improve the detection of metastases, particularly in PCa, where there is a poor correlation between LN size and metastatic involvement . Yoon et al .…”
Section: Discussionmentioning
confidence: 99%
“…In a previous survey on PCa conducted by the International Society of Urological Pathology (ISUP), 27% of members submitted the entire PLND specimen . Not surprisingly, studies have shown that total embedding can increase the nodal yield following RP and RC and may improve the detection of metastases, particularly in PCa, where there is a poor correlation between LN size and metastatic involvement . Yoon et al .…”
Section: Discussionmentioning
confidence: 99%
“…Formalin-fixed LN specimens were completely embedded in paraffin and processed according to the protocol described by Rais-Bahrami et al [22]. Paraffin-embedded sections of thickness 2 µm were routinely stained with haematoxylin and eosin, and where required immunohistochemical staining with a pancytokeratin antibody (AE1/3, dilution 1:100) was performed to exclude micrometastases.…”
Section: Methodsmentioning
confidence: 99%